2019
DOI: 10.1038/s41590-019-0421-2
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral TREM1 responses to brain and intestinal immunogens amplify stroke severity

Abstract: Stroke is a multiphasic process in which initial cerebral ischemia is followed by secondary injury from immune responses to ischemic brain components. Here we demonstrate that peripheral CD11b + CD45 + myeloid cells magnify stroke injury via activation of triggering receptor expressed on myeloid cells 1 (TREM1), an amplifier of proinflammatory innate immune responses. TREM1 was induced within hours after stroke peripherally in CD11b + CD45 + cells trafficking to ischemic brain. TREM1 inhibition genetically or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 62 publications
2
97
0
1
Order By: Relevance
“…Although several mechanisms ( 43 ) (such as the production of reactive oxygen species and the release of metalloproteinases) have been attributed to neutrophils, the existence of neuroprotective N2 neutrophils has also been reported ( 44 ). A recent study in mice identified the triggering receptor expressed on myeloid cells (TREM)-1 as an interesting target for pharmacotherapies aimed at reducing the pro-inflammatory response of peripheral and intestinal myeloid cells after AIS ( 45 ).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although several mechanisms ( 43 ) (such as the production of reactive oxygen species and the release of metalloproteinases) have been attributed to neutrophils, the existence of neuroprotective N2 neutrophils has also been reported ( 44 ). A recent study in mice identified the triggering receptor expressed on myeloid cells (TREM)-1 as an interesting target for pharmacotherapies aimed at reducing the pro-inflammatory response of peripheral and intestinal myeloid cells after AIS ( 45 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…TREM1 is a potent enhancer of innate immune responses, it acts by synergizing with classical PRRs, thus inducing the production of proinflammatory cytokines and chemokines, including IL-8, monocyte chemoattractant protein-1 (MCP-1), MCP-3 and macrophage inflammatory (MIP-1α), and inhibition of IL-10 ( 45 ). Furthermore, neurotoxic mechanisms activate the release of pro-inflammatory cytokines such as interleukin-21 from cluster of differentiation (CD)-4 + T cells within 24 h after AIS ( 46 ) and IL-17 from γδT-cells ( 47 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…A reduced diversity of microbiota species and an overgrowth of bacteria are the main features of post-stroke microbiota dysbiosis, which polarizes immune cells both in gut and brain to adopt a pro-inflammatory phenotype, and this may influence the stroke outcome (43). The leaky gut barrier caused by a stroke also leads to the translocation microbiota and metabolites to trigger neuroinflammation and a peripheral immune response (44). Accumulating evidence suggest that altering the gut microbiota composition can shape the local immune environment in the brain in favor of neurogenesis and axon growth after stroke because lymphocytes have been shown to migrate from gut to brain after stroke: Gut-derived CD4 + T cells migrate to meninges and control the balance between M1 and M2 microglia/macrophage after ischemic injury (45).…”
Section: Gut Microbiota As Potential Regulators Of Neural Repairmentioning
confidence: 99%
“…Remarkably, novel studies unraveled that in experimental ischemia/stroke, a dramatic up-regulation of TREM-1 occurs firstly in the gut and subsequently in the CNS. This is dependent on the adrenergic nervous system, providing a link between CNS disease, systemic inflammation, and gut barrier dysfunction [62,63]. In detail, in experimental stroke, TREM-1 is up-regulated in myeloid cells within the spleen and intestine, from where it reaches the brain to magnify stroke injury [63].…”
Section: Role Of Trems In Neurodegenerative Disordersmentioning
confidence: 99%
“…This is dependent on the adrenergic nervous system, providing a link between CNS disease, systemic inflammation, and gut barrier dysfunction [62,63]. In detail, in experimental stroke, TREM-1 is up-regulated in myeloid cells within the spleen and intestine, from where it reaches the brain to magnify stroke injury [63]. Within the lamina propria, noradrenergic-dependent increases in gut permeability occur, which contribute to inducing TREM-1 on activated macrophages, further increasing epithelial permeability, facilitating bacterial translocation within the CNS and exacerbating neurological damage [62,63].…”
Section: Role Of Trems In Neurodegenerative Disordersmentioning
confidence: 99%